Anaerobic and Aerobic Metabolic Capacities Contributing to Yo-Yo Intermittent Recovery Level 2 Test Performance in Australian Rules Footballers - Mitchell Mooney; Ryan Worn; Matt Spencer; Brendan J. O’Brien (Sports, 2024)
This study aimed to identify the aerobic and anaerobic metabolic performance capacities contributing to Yo-Yo Intermittent Recovery level 2 (Yo-Yo IR2) test performance. Nineteen recreational Australian footballers completed a Yo-Yo IR2 test, and on another day a treadmill peak oxygen uptake (VO2peak) and maximal accumulated oxygen deficit test in a randomised counter-balanced order. The maximal accumulated oxygen deficit (MAOD) procedures included 5 × 5 min sub-maximal continuous runs at progressively higher speeds whilst VO2 was recorded; thereafter, speed was incrementally increased to elicit VO2peak. After 35 min of rest, participants ran at a speed equivalent to 115% of VO2peak until exhaustion, at which point expired air was collected to determine maximal accumulated oxygen deficit. Relationships between variables were assessed using Pearson’s correlation and partial correlations. Maximum aerobic speed, relative intensity, and VO2peak were significantly correlated with Yo-Yo IR2 performance. High Yo-Yo IR2 performers also had higher MAS, relative intensity, and VO2peak levels. However, when higher maximum aerobic speed, relative intensity, and VO2peak were controlled for each other and analysed independently, neither maximal aerobic speed nor VO2peak correlated with Yo-Yo IR2 performance. Yo-Yo IR2 performance is the result of a complex interaction between several variables. Training programs should primarily focus on improving VO2peak, maximal aerobic speed, and relative intensity to optimize Yo-Yo IR2 test performance.